Observer based direct control strategy for a multi-level three phase flying-capacitor inverter. (May 2019) - Laamiri, S.; Ghanes, M.; Santomenna, G.
Abstract: Thanks to the series of connections taking place in commutation cells, flying-capacitor converters provide a means of increasing power and voltage, better harmonic content with reduced d v ∕ d t and can be reconfigured in order to work in degraded mode. However, all these advantages come to the price of a more complex structure, which leads to more complex control strategies. On the other hand, capacitor voltages sensors which are usually expensive, bulky and can degrade the system's reliability, especially in a hostile environment. To overcome both problems (control complexity and capacitor voltages measurements) and motivated by an industrial application with GS Maintenance company, a simple control strategy and an adaptive observer, scalable to any number of cells, are designed for a multi-level DC bus midpoint three-phase FCI (Flying-Capacitor Inverter). Furthermore, the stability of the proposed control strategy and observer design is proved by means of Lyapunov theory. Finally, the good performance under load resistance, cells capacitor and input variations through experimental results is showed in case of a DC bus midpoint 3-cells 4-levels three phase FCI.